Sarawak traditional handicraft ordering system / Devora Puyang Robin - Robin, Devora Puyang (2023)
Sarawak Traditional Handicraft Ordering System is an e-commerce website where customers can view the consumer review and buy the handicraft product. Sarawak Traditional Handicraft Ordering System was created to address the problems that customers have such as customer difficulty to get shop information that sells the local handicraft. In addition, it can be complicated for a customer to compare products sold by different sellers. Last but not least, the seller ease to missed order from the customer. Nevertheless, this project must accomplish three goals which is to identify the current process, the problems and the requirement for the website, to design and develop an ordering platform for online shops and marketplace and to evaluate the functionality of the website. The SDCL Waterfall model has also been adopted by the researcher in this system development project. Besides that, each phase has determined different activities during the system development. Additionally, the Customer Relationship Management (CRM) theory and Ten Usability Heuristics theory that was implemented in this development system which used to improve the system design in order to met customer needs. The testing phase will be completed using test planning, which is used in system testing to find errors and test functionality which is used to evaluate the customer experience with the system.